Daily activities and self-esteem among university students with and without ADHD - Eryn H. Turner; Seth C. Harty (Frontiers in Psychiatry)
IntroductionA diagnosis of ADHD has been repeatedly associated with low self-esteem in university students. Low self-esteem is associated with a range of negative outcomes including poor social function, increased psychopathology, and low academic self-efficacy. This study examined associations between ADHD, self-esteem, and daily activities in university students.MethodsA total of n =125 university students from New Zealand (50 meeting diagnostic criteria for ADHD) completed a survey measuring ADHD symptoms, self-esteem, and variables associated with self-esteem as well as a seven-day ecological momentary assessment survey measuring momentary self-esteem, mood, and current activity.ResultsADHD was associated with a range of negative outcomes including low self-esteem, low general and academic self-efficacy, and high levels of mental distress. Global self-esteem was associated with momentary self-esteem. Differences between students with and without ADHD were observed both in momentary self-esteem ratings and the frequencies of endorsed activities. In both groups, decreased momentary self-esteem was associated with being alone and procrastinating. For other activities, a differential pattern of momentary self-esteem increases was observed across groups.DiscussionThis study provides support for the view that self-esteem is best conceptualised as both a stable trait and a state, fluctuating in response to daily events. Notably, this study also provides evidence that engagement in specific activities is associated with dynamic elevations in self-esteem among university students meeting diagnostic criteria for ADHD.